1/3( 4 - 5x - 1)
= (1/3)(4 + - 5x + - 1)
= (1/3)( 4) + (1/3)(- 5x) + (1/3)( - 1)
= 4/3 + - 5x/3 + - 1/3
= - 5x/3 + 1 (Decimal: - 1.666667x + 1)
Hope that helps!!!!
Answer:
Step-by-step explanation:
First you distribute so two times 4Y is 6Y then you multiply the two in the five which gives you 2Y -5 equals 70
A zero in front of the x would make this a difference of two perfect squares. All of the other option would interfere by adding another term.
Answer:
B. logarithms of negative number don't exist